Measuring two proteins to help assess which melanomas are most likely to spread. (2nd January 2020) - Ellis, R.; Tang, D.; Nasr, B.; Greenwood, A.; McConnell, A.; Anagnostou, M.E.; Elias, M.; Verykiou, S.; Bajwa, D.; Ewen, T.; Reynolds, N.J.; Barrett, P.; et al.
Summary: Melanoma is the most deadly skin cancer, with a worldwide incidence that increases year on year. A major unmet need is the discovery of means through which to identify patients with early stage melanoma at high risk of disease progression, meaning it will spread elsewhere in the body. This UK study aimed to determine if the loss of two proteins, AMBRA1 and loricrin, in the skin (upper layer of skin epidermis) overlying a melanoma is able to predict which patients are at risk of disease spread. Initially, levels of AMBRA1 were assessed in melanoma biopsies from 79 patients. Results suggested a reduction or loss of AMBRA1 in the overlying epidermis was associated with a higher risk of disease spread. The ability to predict the risk of melanoma progression was improved by measuring combined levels of epidermal loricrin and AMBRA1 (eAMLo). By studying a further 379 melanoma samples with at least 10 years of follow‐up data (which shows what happened to the patient), the authors found that a stage I (early stage) melanoma in which eAMLo was lost was almost four times more likely to spread than a melanoma with maintained eAMLo. Importantly, patients in which eAMLo was retained (i.e. not lost) only had a 1.7% chance of disease progression. A melanoma's thickness is part of how its stage (progression) is measured, and currently, patients with a melanoma greater than 1mm thick are offered a further investigative test called sentinel lymph node biopsy (SLNB). However, a negative result from this invasive procedure does not provide any additional information about the chance of melanoma spread. Importantly, when eAMLo levels were assessed in melanomas eligible for SLNB, results further revealed eAMLo was better at identifying patients at truly low‐risk of disease spread than SLNB alone. Collectively, this study shows that measuring eAMLo will help to show a patient's true risk of a melanoma progression, which will help to guide their ongoing treatment and monitoring. This summary relates to the study: Epidermal autophagy and beclin 1 regulator 1 and loricrin: a paradigm shift in the prognostication and stratificatee on Cancer stage I melanomas Abstract : Linked Article: Ellis et al. Br J Dermatol 2020; 182 :156–165